Enhance the Grouth and Flowering of Roses (Rosa galica L.) Due to Composted Waste Coffee Powder and Gibberellins Concentration - Elly Kusumawati; Feri Affriadi; Mardhiah Hayati (Syiah Kuala University, 2015)
This study aims to determine the effect of composted waste coffee powder and gibberellins concentration on the growth and flowering of roses (Rosa galica L.) as well as the interaction between the two factors. Research conducted at the Experimental Farm of the Faculty of Agriculture Syiah Kuala University, Banda Aceh. This study used a Randomized Block Design (RAK) in factorial arrangement; there are two factors with three replications. The first factor is composted waste coffee powder consisting of: soil + composted waste coffee powder (1:1), soil + composted waste coffee powder (1:2), sand + composted waste coffee powder (1:1), sand + composted waste coffee powder (1:2). The second factor is the concentration of gibberellins consisting of: 0, 100, 200, and 300 ppm. The results showed that the composition of the growing media composted waste coffee powder has no significant effect on all parameters observed. Planting media composition tends to be better found in sand + composted waste coffee powder (1:1). The concentration gibberellin very significant effect on the number of branches at the age of 60 days after planting (DAP), significant effect on plant height, stem diameter and number of rose plants flower, at the age of 45 and 60 DAP. The best growth and flowering of roses was found on concentration of 200 ppm gibberellin. There was no significant interaction between composted waste coffee powder with gibberellin concentration on all parameters observed